The Influence of Differentiated Learning Methods on Student Motivation and Learning Outcomes - Hasibuan, Nur Khofifah; Yeli, Salmaini; Zaitun, Zaitun (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
Motivation is important in improving learning outcomes. One of the methods used by MTs N 1 Padang Lawas is the application of differentiated learning methods. Teachers use this method to increase student motivation and learning outcomes. This research aims to determine the influence of differentiated learning methods on student motivation and learning outcomes at MTs Negeri 1 Padang Lawas. The type of research is a quantitative experimental method with a pre-test and post-test design carried out at MTs Negeri 1 Padang Lawas. The results of this research are 1) There is an influence of differentiated learning methods on students' learning motivation on pre-test and post-test data with a significant value obtained of 0.000 < 0.05 while the T count is 22.032 > 1.970 with a positive coefficient value. 2) there is an influence of differentiated learning methods on student learning outcomes obtained with a significant value of 0.000 < 0.05 while the T count is 25.928 > 1.970 with a positive coefficient value. 3) there is an influence of differentiated learning methods on student motivation and learning outcomes on post-test data on motivation and learning outcomes with T calculated > T table at a significant level of 5% (19.909 > 1.970). The findings of this research have the effect of increasing student motivation and learning outcomes by using differentiated learning methods.